IPDLN Workshop: Opportunities for Cross-Country Comparisons of Linked Administrative Education and Health Data - Andersen, Anne-Marie Nybo; Aradhya, Siddartha; Bilsteen, Josephine Funck; Bowden, Nick; Early, Erin; Falster, Kathleen; Flatø, Martin; Fleming, Michael; French, Rob; Hagemann, Erika; Harron, Katie; Keating, Jen; et al. (International Journal of Population Data Science, 2024)
Objectives To understand how we can better initiate and run international collaborations to deliver tangible and impactful findings using population-wide linked health and education data. Approach Representatives from 14 countries (America, Australia, Canada, Chile, Denmark, England, Finland, Germany, New Zealand, Northern Ireland, Norway, Scotland, Sweden, Wales) summarised the potential for research using their linked administrative health and education data. The scope for collaboration and comparison of research findings across countries was explored. Results Several substantive research themes emerged, including the quantifying of differences in educational outcomes by health conditions and other early life factors, using health data to better identify and explore the special educational needs identified in educational records, using linked health and education data to identify and explore reasons for absenteeism from school. Conclusions The workshop showcased the primary themes for research and the data assets available within each country for comparative work. Further work is required to more robustly document the available detail within these datasets, collaboratively develop protocol templates for comparative studies, and develop pilot, proof of concept, studies.